New records and host associations of the tick Ixodes apronophorus and the first detection of Ehrlichia sp. HF in Romania - Andersson, Martin O.; Radbea, Gabriel; Frangoulidis, Dimitrios; Tomaso, Herbert; Rubel, Franz; Nava, Santiago; Chitimia-Dobler, Lidia (2018)
Ixodes (Ixodes) apronophorus is a neglected tick species and its geographical distribution, host associations, and role as a disease vector are not well known. We collected I. apronophorus from several locations in Romania. Morphological identification of ticks was confirmed by analysis of 16S rDNA and 12S rDNA gene sequences. We report new host associations of I. apronophorus, which was collected from dogs, foxes, and a hare—all new hosts for this tick species in Romania. Furthermore, we report for the first time occurrence of Ehrlichia sp. HF in I. apronophorus. Ehrlichia sp. HF was identified by sequencing a part of the 16S rDNA gene and was found in 16% (3/19) of the tested ticks. Ehrlichia sp. HF has not been previously reported in Eastern Europe and seems to have a much larger geographic distribution than previously known. Currently, it is unknown whether I. apronophorus is a competent vector for Ehrlichia sp. HF, or if the findings in this study represent infection in the hosts, namely dogs and fox.